Gender Issues and Their Impact on Guest Complaint Handling Effectiveness in Budget Hotels within Tourism Industry - Agung Edy Wibowo; Karium Jackson.M, Nainggolan (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the influence of gender on guest complaint handling in budget hotels in Batam City, Indonesia—an industrial centre that has also become a growing tourist destination. A total of 182 respondents were selected through purposive sampling, and data analysis was conducted using Smart PLS. The research focuses on four service quality dimensions: assurance, empathy, responsiveness, and reliability. Results indicate that gender significantly moderates the relationships between assurance, empathy, and responsiveness with complaint handling effectiveness, but does not moderate reliability. Specifically, male respondents show a stronger moderating effect on responsiveness, while female respondents exhibit stronger moderating effects on assurance and empathy. No significant moderating role of gender was found for reliability. These findings highlight the importance of considering gender differences in service strategies to enhance guest satisfaction and complaint resolution in the budget hotel sector